Branding of Information: Necessity of Branding in Library and Information System in the forthcoming Decades and the Indian Scenario - Chakrabarty, Mahuya; Adhikari, Atanu (Journal of Information and Knowledge, 2014)
Branding is a core mnemonic device used by the corporates to expand their business. Multi-disciplinary research in differ-ent fields and introduction of new technology causes information explosion. Development of information technology has also removed the geographical boundaries of accessing and retrieving information efficiently and effectively. This paper makes an attempt to identify the necessity of branding in the information world and its significance and the importance of users' choice and preferences. This paper also discusses the steps to be followed by the library or information canters to develop a marketing culture. It states the risk and difficulties of the information service branding and discuss the essential characteristics to be considered in establishing consistency in quality of services. This paper also includes the branding techniques already used by the library personnel for acquiring documents or information, for collection development of their own institution and the Indian scenario for branding of information.